The Angiotensin Converting Enzyme Insertion/Deletion polymorphism is not associated with an increased risk of death or bronchopulmonary dysplasia in ventilated very low birth weight infants - Baier R John; Loggins John; Yanamandra Krishna (BMC, 2004)
Abstract Background The ACE gene contains a polymorphism consisting of either the presence (insertion, I) or absence (deletion, D) of a 287 bp alu repeat in intron 16. The D allele is associated with increased ACE activity in both tissue and plasma. The DD genotype is associated with risk of developing ARDS and mortality. The frequency of the D allele is higher in patients with pulmonary fibrosis, sarcoidosis and berylliosis. The role of this polymorphism has not been studied in the development of BPD in the premature newborn. Methods ACE I/D genotype was determined in 245 (194 African-American, 47 Caucasian and 4 Hispanic) mechanically ventilated infants weighing less than 1250 grams at birth and compared to outcome (death and/or development of BPD). Results The incidence of the D allele in the study population was 0.58. Eighty-eight (35.9%) infants were homozygous DD, 107 (43.7%) were heterozygous ID and 50 (20.4%) were homozygous II. There were no significant differences between genotype groups with respect to ethnic origin, birth weight, gestation, or gender. There was no effect of the ACE I/D polymorphism on mortality or development of BPD (O2 on 28 days or 36 weeks PCA). Secondary outcomes (intraventricular hemorrhage and periventricular leukomalacia) similarly were not influenced by the ACE ID polymorphism. Conclusions The ACE I/D polymorphism does not significantly influence the development of BPD in ventilated infants less than 1250 grams.